Land acquisiton policy in Bangladesh: a case study on the land acquisition activities of Tangail district - Talukder, Md. Mahbub Alam (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.